Women in Serbian Advertising - Popesku, Mihajlo (2008)
This study is an attempt of valuable contribution to the gender issues literature since it explains portrayal and appearance of women in advertising within the context of Serbia, a country in transition. Having in mind this extremely turbulent and unique context, it is of particular interest to re-examine gender issues hypotheses based on the findings from western countries, due to the fact that knowledge gained from these contexts may not be fully applicable to the Serbian context.